2016
DOI: 10.1177/0886260516646090
|View full text |Cite
|
Sign up to set email alerts
|

On the Lived Experience of Sex Offenders’ Therapists: Their Perceptions of Intrapersonal and Interpersonal Consequences and Patterns of Coping

Abstract: In the last two decades, there has been a growing understanding that the therapeutic encounter with sex offenders takes a cost and has consequences on therapists. Despite the increasing research on the consequences of treating sex offenders, these studies in fact, have merely described the consequences, without providing an outlook for how therapists cope with them. The study presented in this article was part of a larger qualitative research project conducted among social workers, using in-depth semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 39 publications
(78 reference statements)
1
16
1
Order By: Relevance
“…Several authors have, however, reported either low levels of stress and/or a variety of positive experiences among sex offender therapists ( Carmel & Friedlander, 2009 ; Elias & Haj-Yahia, 2016 ; Ennis & Horne, 2003 ; Hatcher & Noakes, 2010 ; Moore, 2016 ; Scheela, 2001 ; Shelby, Stoddart, & Taylor, 2001 ). In example, Carmel and Friedlander (2009) obtained low mean scores on stress-related measures, yet high levels of compassion satisfaction, indicating that the 106 therapists, who returned their questionnaire, generally enjoy their work.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several authors have, however, reported either low levels of stress and/or a variety of positive experiences among sex offender therapists ( Carmel & Friedlander, 2009 ; Elias & Haj-Yahia, 2016 ; Ennis & Horne, 2003 ; Hatcher & Noakes, 2010 ; Moore, 2016 ; Scheela, 2001 ; Shelby, Stoddart, & Taylor, 2001 ). In example, Carmel and Friedlander (2009) obtained low mean scores on stress-related measures, yet high levels of compassion satisfaction, indicating that the 106 therapists, who returned their questionnaire, generally enjoy their work.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using qualitative methodologies did, however, provide insight into this. Elias and Haj-Yahia (2016) , who argued that existing research has merely sought to describe the consequences of work with sex offender, while neglecting how therapists perceive and cope with them, made the latter the aim of their research. According to one participant, negative impact was perceived to be a consequence of being confronted with their clients’ offences: “The emotions I carry with me are difficult.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations